Fungal volatiles mediate cheese rind microbiome assembly. (20th September 2020) - Cosetta, Casey M.; Kfoury, Nicole; Robbat, Albert; Wolfe, Benjamin E.
Summary: In vitro studies in plant, soil, and human systems have shown that microbial volatiles can mediate microbe–microbe or microbe–host interactions. These previous studies have often used artificially high concentrations of volatiles compared to in situ systems and have not demonstrated the roles volatiles play in mediating community‐level dynamics. We used the notoriously volatile cheese rind microbiome to identify bacteria responsive to volatiles produced by five widespread cheese fungi. Vibrio casei had the strongest growth stimulation when exposed to all fungi. In multispecies community experiments, fungal volatiles caused a shift to a Vibrio ‐dominated community, potentially explaining the widespread occurrence of Vibrio in surface‐ripened cheeses. RNA sequencing identified activation of the glyoxylate shunt as a possible mechanism underlying volatile‐mediated growth promotion and community assembly. Our study demonstrates how airborne chemicals could be used to control the composition of microbiomes and illustrates how volatiles may impact the development of cheese rinds.